الاستفادة من نظام التعليم العام في فنلندا - أبا الخيل، سيرين بنت صالح بن سليمان (كلية الامارات للعلوم التربوية, 2023)
يهدف البحث الحالي إلى التعرف على الأهداف العامة لنظام التعليم العام في فنلندا، واستقصاء العوامل المؤثرة في نظام التعليم العام في فنلندا، والوقوف على مزايا التعليم العام في فنلندا، كذلك طرح أوجه الاستفادة من التعليم العام في فنلندا أثناء جائحة كوفيد 19. واعتمد البحث على المنهج التحليلي للتوصل لنتائج البحث، وقد تبين من خلال النتائج: أن فنلندا تحولت من بلد اقتصاده زراعي إلى بلد ذي اقتصاد معرفي متقدم في مدة قصيرة قرابة ثلاثة عقود، وكان التعليم هو أهم ركيزة في هذا التحول. وقدم البحث عدة توصيات للاستفادة من التعليم العام في فنلندا، ومنها: زيادة الاهتمام بالمتعلم وأن يكون فاعلا ومنتجا في المجتمع وتوفير المعرفة والمهارات الضرورية لمواجهة تحديات الحياة. The current research aims to identify the general objectives of the public education system in Finland, investigate the factors affecting the public education system in Finland, identify the advantages of public education in Finland, as well as put forward the benefits of public education in Finland during the covid-19 pandemic. The research was based on the analytical approach to reach the results of the research, and it was shown through the results that Finland has transformed from a country with an agricultural economy to a country with an advanced knowledge economy in a short period of almost three decades, and education was the most important pillar in this transformation. The research made several recommendations to benefit from public education in Finland, including: increasing interest in the learner to be active and productive in society and providing the necessary knowledge and skills to face life's challenges.
Keywords: السياسات التعليمية -- التعليم العام -- اقتصاد المعرفة -- جائحة كورونا "كوفيد-19" -- المجتمع الفنلندي